HAEMATOLOGICAL PROFILE DERANGEMENTS IN PATIENTS DUE TO NON-RESISTANT AND RESISTANT TYPHOID FEVER: Haematological Profile Derangements - Tashfeen, Sunila; Asif, Naveed; Farooq, Muhammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess and compare the frequency of haematological parameter derangements in patients due to non-resistant and extended drug resistant (XDR) typhoid fever.Study Design: Comparative cross-sectional study.Place and Duration of Study: Pathology Department of Combined Military Hospital Quetta, from Jan to Dec 2019.Methodology: A total number of 172 blood culture Salmonella positive patients irrespective of age and gender were included in this study. Salmonella strains were isolated and grouped further according to their drugs sensitivity. 3ml venous blood was collected from these patients in Ethylene diamine tetra acetic acid container and blood complete count was done by semiautomated haematology analyser XP-100.Results: There were 126 (73%) males and 46 (27%) females with mean age of 17.5 ± 10.3 years. Out of 172 subjects, 106 (61.6%) had non-resistant typhoid and rest 66 (38.4%) were diagnosed with extended drug resistant Typhoid. We compared anaemia, leucopenia and thrombocytopenia between two groups and found anaemia statistically significant with the p-value of 0.001.Conclusion: This study has documented that changes in haematological parameters are significant in typhoid fever and early patients diagnosis, management and disease course can be monitored with them. Patients with significant anaemia and not responding to first line therapy should be considered as a case of extended drug resistant (XDR) Salmonella.